2021
DOI: 10.1007/s10639-021-10706-w
|View full text |Cite
|
Sign up to set email alerts
|

Technology supported learning and pedagogy in times of crisis: the case of COVID-19 pandemic

Abstract: Online teaching within disciplines such as Engineering require experiential learning that equip future graduates with highly intellectual and professional skills to meet the demands of employers and the industry. The outbreak of COVID-19 however, has shifted the academic community into new landscapes that require educators and students to adapt and manage their expectations. Although literature reports on research attempts to study the implications of Covid-19 on the Higher Education curricular, little has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 40 publications
5
62
0
8
Order By: Relevance
“…The findings of the current study showed that even though more than three out of four universities had a CDE or a similar unit before the start of the pandemic, the primary problem they encountered was still the lack of technical infrastructure. This corroborated Ahmed and Opoku's (2021) findings. This might be attributed to the fact that more than half of these CDEs were either inactive or active with a limited number of programs and students.…”
Section: Final Remarkssupporting
confidence: 87%
“…The findings of the current study showed that even though more than three out of four universities had a CDE or a similar unit before the start of the pandemic, the primary problem they encountered was still the lack of technical infrastructure. This corroborated Ahmed and Opoku's (2021) findings. This might be attributed to the fact that more than half of these CDEs were either inactive or active with a limited number of programs and students.…”
Section: Final Remarkssupporting
confidence: 87%
“…The study’s context stems from the fact that more users are exposed to digital devices, particularly teachers/students who are forced to teach and learn in an online environment due to the Covid-19 pandemic (Ahmed & Opoku, 2022 ). In general, users and students are undoubtedly distracted by their use of social media (Mao, 2014 ; Dontre, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all behaviors in virtual learning have been positive. Precisely the lack of certain social skills has resulted in cyberbullying situations [101]. This has affected, in the most extreme cases, the academic performance of students [102].…”
Section: Online Teaching and Its Inference In The Social Problems Of Intercultural Studentsmentioning
confidence: 99%